Penerapan Program Penguatan Pendidikan Karakter (PPK) di Sekolah Menengah Atas Negeri 1 Tuban - Candrakusuma, Shandy Dwisaksana Aditya; Astutik, Sri; Subekti, Subekti (Pamulang university, 2023)
The Indonesian government has implemented the Character Education Strengthening (PPK) Program at SMA Negeri 1 Tuban to measure students' soft skill abilities and address declining morality. The program aims to provide character education as a foundation for students before higher education or entering society. The research examines character education at SMA Negeri 1 Tuban using an empirical legal research method, comparing real phenomena with existing theories. The study employs a qualitative approach, analyzing the implementation of the PPK program and legal protection for teachers. Secondary data, including student data, the learning curriculum, and relevant legal sources, were collected through literature studies. The research reveals that SMA Negeri 1 Tuban has integrated character education into the curriculum and student affairs. However, there is a need for improved legal protection for teachers in implementing character education. Despite existing laws, disciplinary processes against students have resulted in legal cases involving teachers. It is suggested that more specific laws be established to protect teachers in every curriculum program. When disciplining students, teachers should consider the limits to avoid worsening the impact on students. By doing so, the learning process can be enhanced to achieve better results.